2015
DOI: 10.2497/jjspm.62.400
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Vibration Damping Mechanisms of Cu-Sn/Al<sub>2</sub>O<sub>3 </sub>Composite Material by Frequency Response Function of FFT Analyzer

Abstract: In the fields of an eco-friendly automobile, an advanced industrial machine, and a precision electronic device, controlling of vibration damping behavior of the sintering parts obtained from powder metallurgy is required. In this paper, the vibration behavior of Cu-Sn/Al 2 O 3 composite material made by powder metallurgy was investigated by a FFT analyzer.Cu, Sn, and Al 2 O 3 powders were used as initial substances. The powders were mixed and pressed into a plate shaped compact with 200 MPa. Using a vacuum fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…On the other hand, for Cu-Sn/Al 2 O 3 , Cu-Sn/Graphite sintered composite materials, vibration damping coefficient was depended on the mixing ratio of disperse particle, and twin crystal is introduced in the Cu-Sn matrix phase cause by interface energy between matrix phase and disperse particle, and it was found that vibration damping behavior of Cu-Sn/Al 2 O 3 , Cu-Sn/Graphite sintered composite materials was affected by the twin crystal of Cu-Sn matrix phase 6,7) . However, effect of shape of dispersed particle is not clear yet.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…On the other hand, for Cu-Sn/Al 2 O 3 , Cu-Sn/Graphite sintered composite materials, vibration damping coefficient was depended on the mixing ratio of disperse particle, and twin crystal is introduced in the Cu-Sn matrix phase cause by interface energy between matrix phase and disperse particle, and it was found that vibration damping behavior of Cu-Sn/Al 2 O 3 , Cu-Sn/Graphite sintered composite materials was affected by the twin crystal of Cu-Sn matrix phase 6,7) . However, effect of shape of dispersed particle is not clear yet.…”
Section: Introductionmentioning
confidence: 99%
“…The powders and fiver were mixed, and Cu/Sn/Carbon fiber premixed powder was prepared. The mixing ratio of Cabon fiber were set to 5%, 10% as same manner of the previous paper 6,7) . These premixed powder was pressed with 200 MPa, and plate shaped compacts of L = 120 mm, W = 20 mm, t = 10 mm were made.…”
Section: Preparation Of Cu-sn/carbon Fiber Sintered Composite Materialsmentioning
confidence: 99%
See 3 more Smart Citations